As lutas pela humanização da assistência ao parto e ao nascimento: um estudo de caso sobre a Maternidade Leonina Leonor Ribeiro - Fernanda Araujo Pereira (2022)
This research develops a case study about the Leonina Leonor Ribeiro Maternity. It is a public health equipment built in Belo Horizonte to assist users according to the humanized model of childbirth care. After successive changes of municipal governments, the Leonina Leonor Ribeiro Maternity was never inaugurated, until, more than a decade after its construction, the Municipality began its dismantling. So, this paper aims to map the political-legal tensions and disputes that this case unveils as it is part of the paradigm shift processes in childbirth care in the city. The empirical research methodology selected was case study, which I develop from documentary databases. To evaluate the quality of the documents, I make use of four criteria: authenticity, credibility, representativeness and meaning. To analyze the content of these sources, I employ the adopted theoretical frameworks. I start from the idea that the hegemonic obstetric care model is essentially inadequate, risky and violent, as well violates women's rights. In opposition, the movements for humanization claim an assistance based on scientific evidence and care, and also guarantor and promoter of fundamental rights. I also adopt Critical Theory of the Constitution as a reading key, since it allows discussing the case as illustrative of the experience of constitutional normativity, in which meanings of rights are tensioned and disputed interpretatively in the public sphere. Then, I build a narrative that intends to demonstrate that in the route of the non-implementation of the Leonina Leonor Ribeiro Maternity, the Municipality has retrogressed in its pioneering history in the propulsion of the humanized delivery and birth care. I map some political-legal tensions and disputes that were experienced in this process, always under the pressures of the systemic imperatives of the capitalist economy and bureaucratic administration. I believe that this setback is due to the progressive closing of municipal governments to the struggles for humanization, associated with the defense of corporative interests that are contrary to the care transformations historically disputed. At the end, I complement the case study proposal with the outline of a reflection on its potential for exemplary of national movements for paradigm shifts in obstetric and neonatal care.